Effects of single bolus dose of intravenous Dexmedetomidine on intrathecal hyperbaric Bupivacaine: a randomized double blind placebo controlled trial - Reddy, Manjunath; Narayanappa, Archana Byadarahalli; Babu, Sreenivasa (Journal of Society of Anesthesiologists of Nepal, 2016)
Background: To prolong the effect of spinal anaesthesia into the postoperative period many pharmacological agents are being used intrathecally and intravenously. The present study was designed to assess the effects of single bolus dose of intravenous Dexmedetomidine on spinal anaesthesia and analgesia in patients undergoing lower abdominal surgeries under spinal anaesthesia with 0.5% Hyperbaric Bupivacaine. Methods: One hundred patients posted for lower abdominal surgeries under spinal anaesthesia were randomly allocated to two groups. Group D (study group) patients received single bolus dose of 0.5mcg/kg of intravenous Dexmedetomidine and Group C (control group) received 10ml of normal saline. Variation in the onset, duration of sensory and motor level, duration of analgesia, effect on sedation and side effects were recorded. Results: The duration of sensory block and two segment regression was significantly prolonged in Group D (189.90±7.66 minutes, 104±20.6 minutes) as compared to Group C (145.60±11.98 minutes, 75±22.5 minutes). The onset of sensory block was earlier in Group D then compared to Group C which was statistically significant. The duration of analgesia in Group D (218.8 ± 11.36 minutes) was prolonged when compared to Group C (178.6±17.96 minutes). Sedation score and incidence of bradycardia was high in Group D when compared to Group C. Conclusion: Single bolus dose of IV Dexmedetomidine prior to spinal anaesthesia prolongs the duration of sensory block and duration of analgesia with satisfactory arousable sedation and acceptable side effects.